Biosynthesis of zinc oxide nanoparticles by Pichia kudriavzevii GY1 and their biomedical properties - Amin, Boroumandmoghaddam (2018)
In the field of nanotechnology, the use ofvarious biological materials instead oftoxic chemicals for the synthesis of nanoparticles, has merited substantial attention. The use of toxic compounds limits their applications especially in biomedical field. To overcome the problem of toxicity in synthesis, safe eco-friendly green procedures have a major role for producing nanoparticles. Among the many possible bio resources, biologically active products from fungi and yeast represent high potential for this purpose. The present research aims to study the potential ability of a new yeast strain, Pichia kudriavzevii, in the synthesis of zinc oxide nanoparticles (ZnONPs) in order to evaluate their physical and biomedical properties. Zinc oxide nanoparticles (ZnO-NPs) were synthesized by a green method using simple precursor from the solution consisting of zinc acetate and the fungal cell-free filtrate of Pichia kudriavzevii GYl.The effect of reaction time (12, 24 and 36 h) on the structure of the resulting ZnO nanoparticles was investigated. The samples were characterized using Fourier transform infrared (FTIR), ultraviolet-visible (UV-vis), x-ray diffraction (XRD), transmission electron microscope (TEM), field emission scanning electron microscope (FESEM), Photoluminescence (PL) and biomedical tests as free radical scavenging activity, cytotoxicity, antibacterial and anticancer activities. From the XRD and TEM results, the ZnO-NPs with a hexagonal wurtzite structure and a particle crystal size of ~10-61 nm were formed at different reaction times. The most favourable nanosized structure with the lowest defect concentration was obtained at intermediate duration (24 h). The ZnO-NPs showed strong DPPH free radical scavenging and a dose dependent toxicity with non-toxic effects on Vero cells for concentrations below 190 ug/ml., The antibacterial tests reveal a favourable antibacterial effect for those ZnO-NPs prepared at intermediate duration. The anticancer activity ofbiosynthesized ZnO-NPs on breast cancer cells (MCF-7) was determined using MTT assay. Cell cycle analysis and the mode of cell death were evaluated using a flow cytometry instrument. Quantitative real-time-PCR (qRT-PCR) was employed to investigate the expression ofapoptosis in MCF-7 cells. ZnO NPs were cytotoxic to the MCF-7 cells in a dose-dependent manner. The 50% growth inhibition concentration (IC50) of ZnO NPs at 24 h was 121 ug/ml., Cell cycle analysis revealed that ZnO NPs induced sub-Gj phase (apoptosis), with values of 1.87% at 0 ug/ml, (control), 71.49% at 1C25, 98.91% at IC50, and 99.44% at IC75· Annexin V/propidium iodide (PI) flow cytometry analysis confirmed that ZnO NPs induce apoptosis in MCF-7 cells. The pro-apoptotic genes p53, p2I, Bax, and JNK were upregulated, whereas anti-apoptotic genes Bcl-2, AKTl, and ERKII2 were downregulated in a dose-dependent manner. The arrest and apoptosis ofMCF-7 cells were induced by ZnO NPs through several signalling pathways. Generally, the study has successfully contributed to the knowledge on the discovery of using fast-growing microorganism as a novel green approach in producing nanoparticles as new materials for the current innovation of bionanotechnology field particularly for medical applications.